Contemporary Employability Skills Needed for Learners to Succeed in the Civil Technology Field in the 4IR Era - Mtshali, Thokozani Isaac; Ramaligela , Sylvia Manto (Journal of Technical Education and Training, 2020)
The contribution of Civil Technology to the Fourth Industrial Revolution (4IR) is largely dependent on whether learners can acquire the necessary knowledge and skills that will make them employable in this field. The 4IR is characterised by rapid technological advances which are changing the face of many industry sectors. Competition is at an all-time high and the need to keep pace with technological shifts has never been so great. Not surprisingly, Civil Technology teachers have a crucial role to play in ensuring that learners are able to confidently make the transition from the classroom to the world of work. In this regard, teachers must have the ability to stimulate learners’ interest and nurture their talents in one or more Civil Technology specialisation/s, but they themselves must have sufficient knowledge and skills if they are to be effective educators. The purpose of the study was to explore what contemporary employability skills are needed for learners to ultimately succeed in the Civil Technology field in the 4IR era. An explanatory sequential mixed-method approach was followed, using both quantitative and qualitative research methods. A key finding was that although Civil Technology teachers are well aware of the importance of remaining responsive to industry needs in the 4IR era, they faced many personal and administrative challenges when it came to actually developing the necessary skills among their learners. Teachers also displayed a general lack of awareness of the value that Civil Technology could deliver to companies, entrepreneurs and the economy as a whole. The study lifted the lid on an important, but until now neglected, area of research which warrants more in-depth investigations, particularly how to bring teachers up to speed in a fast-changing environment.